2021
DOI: 10.1021/jacs.1c02868
|View full text |Cite
|
Sign up to set email alerts
|

AoiQ Catalyzes Geminal Dichlorination of 1,3-Diketone Natural Products

Abstract: Enzymes that can perform halogenation of aliphatic carbons are of significant interest to the synthetic and biocatalysis communities. Here we describe the characterization of AoiQ, a single-component flavin-dependent halogenase (FDH) that catalyzes gem-dichlorination of 1,3-diketone substrates in the biosynthesis of dichlorodiaporthin. AoiQ represents the first biochemically reconstituted FDH that can halogenate an enolizable sp 3 -hybridized carbon atom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Subsequent heterologous expression work, however, showed a different NRPKS DiaA, which is clustered with AoiQ, is involved in synthesizing the coumarin core. 37 DiaA synthesizes a 1,3-diketone containing substrate that can be halogenated by AoiQ with canonical flavin-dependent halogenation mechanism via an enolate intermediate. Nonenzymatic deacetylation and short-chain dehydrogenase/reductase (SDR)-catalyzed ketoreduction afforded dichlorodiaporthin 3 (Fig.…”
Section: Overview Of Heterologous Expression Of Fungal Natural Productsmentioning
confidence: 99%
“…Subsequent heterologous expression work, however, showed a different NRPKS DiaA, which is clustered with AoiQ, is involved in synthesizing the coumarin core. 37 DiaA synthesizes a 1,3-diketone containing substrate that can be halogenated by AoiQ with canonical flavin-dependent halogenation mechanism via an enolate intermediate. Nonenzymatic deacetylation and short-chain dehydrogenase/reductase (SDR)-catalyzed ketoreduction afforded dichlorodiaporthin 3 (Fig.…”
Section: Overview Of Heterologous Expression Of Fungal Natural Productsmentioning
confidence: 99%
“…To date, the majority of the characterized halogenases are flavin‐dependent halogenases (FDHs) and are associated with aromatic halogenation reactions [67] . Halogenases fused with other catalytic enzymes are rare, with limited examples including the intriguing AoiQ, characterized from A. oryzae RIB40 [63–64] …”
Section: Flavoprotein and Methyltransferase Fused Enzymesmentioning
confidence: 99%
“…To gain further insights that how AoiQ catalyzes chlorination on an unactivated carbon atom, Liu and co‐workers reexamined aoiQ and its nearby genes [64] . They found that the aoiQ gene lies in the middle of a different PKS gene cluster ( dia ) (Figure 11), which encodes a NR‐PKS DiaA, a metallo‐β‐lactamase‐like thioesterase (MBβ‐TE) DiaB, a short‐chain dehydrogen‐ase/reductase (SDR) DiaC, and a FMO DiaD [64] .…”
Section: Flavoprotein and Methyltransferase Fused Enzymesmentioning
confidence: 99%
“…The following are available online at https://www.mdpi.com/article/10 .3390/jof8040355/s1: all experimental details including growth media, buffers, enzyme, and antibiotic solutions; bacterial and fungal strains; vectors and oligonucleotides; tabulated NMR data; NMR spectra; and HRMS data. References [25,[28][29][30]32,33,45,[52][53][54][55][56][57][58][59][60][61][62] are cited in Supplementary Materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%